Intellectual property rights in the geopolitics of knowledge of the global knowledge society - Lander, Edgardo (2016)
This text analyzes, from the perspective of the geopolitics of knowledge, the significance of the new transnational regimes of intellectual property protection that in recent years have come to form part of the institutional and legal order of global society. Its emphasis is on the oppositional interests that exist between transnational companies and the in-habitants of the South of the planet.